Symposium 3: International Teamworking and eLearning Design - Spencer-Oatey, Helen; Tang, Min (Proceedings of the International Conference on Networked Learning, 2006)
This paper focuses on international teamworking issues that arose in the initial pilot projects of the eChina~UK Programme. The authors collected a range of data over a 3 year period, including written records of meetings and email exchanges. In addition, they conducted two rounds of in-depth interviews with all the primary team members. This paper presents the findings that are most pertinent to effective teamworking for the design of eLearning courses, particularly in relation to project management. The authors identify important lessons for the effective management of international eLearning design projects that have emerged from their findings.